Un-Dutching the Delta Approach: network management and policy translation for effective policy transfer - Ellen Minkman; Arwin van Buuren; Victor Bekkers (International Review of Public Policy)
This study identifies network management as a facilitator of effective policy transfer. We reconstruct the unconventional collaboration between Dutch private-sector experts and national governments of Vietnam and Bangladesh to develop multi-sectoral, long-term strategies (‘delta plans’). We identify the network management strategies used by the Dutch actors and use these to explain how problem perceptions of state and non-state actors were aligned in order to define solution pathways. Based on these cases, we argue that network analysis is a tool for policy transfer studies. This paper further concludes that the ‘soft’ nature of the transferred policy (in the form of principles, norms and ideas) increased its transferability, as being ambiguous and abstract left room for interpretation and translation to the local context.